2003
DOI: 10.1191/0748233703th191oa
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effects and skin injury after experimental dermal exposure to monochloroacetic acid

Abstract: There have been many fatal occupational accidents of skin exposure to monochloroacetic acid (MCA). However, there have been no reports of dermatological findings and the lethal consequences have not yet been demonstrated. Therefore, harmful local and systemic effects were investigated after dermal exposure to MCA. A 0.5 mL aliquot of MCA solution (40% w/w) was applied to the abdominal skin of ten 10-week-old male SD rats under anesthesia. The exposure area (25 x 25 mm2) was 1.6% of the total surface area. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…Although glyoxylate is the major primary metabolite of DCA, treatment of animals with high doses of DCA has resulted in detection of small amounts of monochloroacetate (MCA) in blood and urine (Shroads, et al, 2008). The concentrations were low, however this was of concern because MCA is neurotoxic (Berardi, et al, 1987; Lu, et al, 2015) and toxic to the liver and kidney (Dote, et al, 2003). Further discussion of the mechanism of toxicity is presented in section 11.4.…”
Section: Biotransformation Of Dca Role Of Gstz1mentioning
confidence: 99%
“…Although glyoxylate is the major primary metabolite of DCA, treatment of animals with high doses of DCA has resulted in detection of small amounts of monochloroacetate (MCA) in blood and urine (Shroads, et al, 2008). The concentrations were low, however this was of concern because MCA is neurotoxic (Berardi, et al, 1987; Lu, et al, 2015) and toxic to the liver and kidney (Dote, et al, 2003). Further discussion of the mechanism of toxicity is presented in section 11.4.…”
Section: Biotransformation Of Dca Role Of Gstz1mentioning
confidence: 99%
“…Fullthickness burns to the skin have only been demonstrated during dermal exposure in experimental animals to MCA. 3 This case is the first one reported of a human full-thickness burn after MCA application; the injury most likely resulted from the high concentration used in combination with curettage and the long duration of contact which included reapplication. A case of partial-thickness burns after the application of this compound has been reported.…”
Section: Discussionmentioning
confidence: 94%
“…5 The mechanism for this process may be related to the disruption of the tricarboxylic acid cycle. 3 Although our patient initially demonstrated evidence of systemic upset, this rapidly settled, and there was no evidence objective of metabolic organ insult. This upset was probably the result of the small area of contact and the physiological reserve found in a young and fit adult.…”
Section: Discussionmentioning
confidence: 95%
“…The solution, flake, and molten forms are corrosive to the skin and cause protein hydrolysis, inflammation, and cell destruction within tissues 1,4 . It has been reported in an experimental study on rats that MCAA at a concentration of 40% causes serious collagen band destruction in the epidermis and subcutaneous tissues; this observation was shown to be a full‐thickness burn 5 . Numerous case reports of skin exposure to MCAA, causing partial or full‐thickness burn injuries, have been described, most of which were mortal 1,4–7 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to wart treatment, it is used for industrial purposes, such as the synthesis of certain organic chemicals 1,4 . Numerous articles and experimental studies have reported chemical burns and systemic toxicity related to MCAA exposure 1,4–7 . In all of these reported cases, a high MCAA concentration was used.…”
Section: Introductionmentioning
confidence: 99%